Adolescent psychiatry. (New York Basic Books, 1997)
Annual
v.1- v.2. Developmental and clinical studies
Author index: Vols. 1-3. 1971-74, in v. 4.
Cumulative index to nursing & allied health literature $x0146-5554
Index medicus 0019-3879 1978-1995
Psychological abstracts $x0033-2887 $b1974-
Keywords: Adolescent psychiatry; Adolescent Psychiatry -- Collected works; Child development disorders -- Collected works